Laser-induced surface texturing of electrodes for obtaining hydrophobic surfaces in electrochemical ammonia synthesis - Tourunen, Eter (My University, 2025)
Hydrophobicity and coating adhesion are critical surface properties in electrochemical applications, where stainless steel electrodes are often used as structural substrates. Conventional stainless steel surfaces are naturally hydrophilic due to their oxide layer, which limits their suitability without additional modification. Laser surface texturing has emerged as a potential method to improve these properties by creating controlled micro- and nanostructures. The aim of this thesis was to examine whether a 100 W nanosecond fibre laser can be applied to generate hydrophobic surface features and enhance the adhesion of cobalt hydroxide coatings on stainless steel. The experimental design focused on two texture geometries (line and grid patterns) produced at two fluence levels (35 J/mm² and 141 J/mm²), allowing systematic evaluation of the effects of processing parameters. The stainless steel specimens were characterised using a combination of macro imaging, scanning electron microscopy analysis, 3D surface topography and areal roughness measurements. Functional performance was assessed through static contact angle measurements and with tape adhesion tests. Cobalt hydroxide coatings were deposited to investigate coating distribution and interfacial stability on both laser-treated and untreated reference surfaces. Results demonstrated that laser texturing significantly altered surface morphology and wettability. The untreated reference surface was hydrophilic, with a contact angle of 82°, whereas laser-treated surfaces achieved contact angles up to 135° (grid pattern, 35 J/mm²). Line patterns produced anisotropic wetting, with orientation-dependent differences up to 32 %, while grid patterns resulted in isotropic wetting. However, after coating deposition, hydrophobicity was strongly diminished or entirely lost, with the G2 surface showing superhydrophilicity. Roughness analyses confirmed that grid textures produced the most pronounced features (Sa up to 16.4 µm, Sz up to 124 µm), but excessive remelting at higher fluence reduced their effectiveness. Adhesion testing revealed that line textures provided enhanced coating stability (grades 2–3), while grid textures performed poorly, with G2 showing complete detachment (grade 0). SEM analyses further indicated that cobalt hydroxide deposition was less effective on laser-treated surfaces, likely due to oxide formation during processing, whereas the untreated reference surface showed more homogeneous and continuous coating coverage. Future work should focus on optimising laser parameters to balance beneficial roughness with controlled oxide formation, as well as exploring combined surface treatments or alternative deposition strategies to achieve both strong hydrophobicity and reliable coating adhesion. These findings provide new insight into how laser-induced surface structures can be tailored for functional stainless steel electrodes, but also highlight the limitations of cobalt hydroxide deposition on laser-textured substrates.
Keywords: laser surface texturing, nanosecond fibre laser, stainless steel, hydrophobicity, surface roughness, contact angle, coating adhesion, cobalt hydroxide deposition, surface morphology, electrode modification